Pengaruh Peran Account Representative Terhadap Tingkat Kepatuhan Wajib Pajak (Studi Kasus pada KPP Pratama di Kota Bandar Lampung) - Angrita Denziana; Handi Sutanto (Jurnal Akuntansi dan Keuangan, 2015)
Tax receipts have an important role in financing pemerindahan with an average of 70 % until2013.By the application of a system of self assessment in a system of taxation in indonesia taxcompliance become the backbone of that must be intensified by the directorate general oftaxes in collect state revenues.Since the era of the directorate general of taxation modernizebirokasi issued a breakthrough by forming a service of strategic that constitute links or totaxpayers, representatives of the djp namely an account that have service representativefunction and supervision of an obligation taxation taxpayers. A regression model for theanalysis results show that simultaneously, account supervision service and significantlyinfluential representative of the level of compliance by taxpayers.